Social Sustainability and Financial Performance: Accounting-Based Panel Evidence from the Jordanian Manufacturing Sector - Tahat, Odai Abdel Rahman; Buniamin, Sharifah (Indonesian Journal of Sustainability Accounting and Management, 2026)
Emerging-market research continues to insufficiently examine the concept of social sustainability, particularly with respect to its quantifiable financial effects on firm performance. This study investigates the relationship between social sustainability and financial performance among 49 manufacturing companies listed on the Amman Stock Exchange over the period 2018–2024 (N = 343 firm-year observations). A manually constructed Social Performance Index (SPI), derived from systematic content analysis of annual corporate disclosures, serves as the primary independent variable. Employing fixed-effects panel regression with firm-level clustered standard errors, financial performance is evaluated through three complementary and theoretically grounded perspectives: Return on Assets (accounting-based), Tobin's Q (market-based), and the Sustainable Growth Rate (growth-based). The empirical findings consistently demonstrate that enhanced social performance is positively and significantly associated with profitability, market valuation, and internally financed growth, whereas financial leverage exerts a persistent, statistically significant negative influence across all model specifications. These results suggest that investments in employee welfare and community engagement function as strategic intangible resources that strengthen operational efficiency and reinforce corporate legitimacy among external stakeholders. This study contributes a context-sensitive social disclosure framework particularly applicable to institutional environments where standardized ESG rating systems remain absent or underdeveloped. It further offers empirical guidance to support the attainment of the UN Sustainable Development Goals 8 and 12 through responsible corporate conduct and sustainable, long-term value creation in emerging economies.